Multifunctional hydrogels-based therapies for chronic diabetic wound healing - Duarte, Joana (2024)
Chronic diabetic wounds persist as a healthcare challenge and therefore require the use of innovative therapeutic approaches. Among emerging solutions, hydrogels stand out as a promising avenue for diabetic wound healing due to their unique properties and versatile applications, capable of addressing the complex and challenging microenvironment that characterizes such wounds. In this work, through a detailed analysis of relevant experimental studies, we highlight the multifunctionality of hydrogels, namely their ability to promote tissue attachment, prevent scarring, fight infection, attenuate inflammation, facilitate electrical signaling, control bleeding, repair damage autonomously, and exhibit responses tailored to specific wound characteristics. The collective findings from these studies emphasize the promising attributes of hydrogels in addressing diabetic wound healing challenges. By elucidating these crucial insights, this work seeks to lay the groundwork both for academics and industries for the development and implementation of effective hydrogel-based strategies that can significantly improve diabetic wound healing outcomes, offering new hope for patients suffering from chronic diabetic wounds.